Evaluasi Kebijakan Retribusi Parkir di Tepi Jalan Umum Kota Semarang - Hardiansyah Hutabarat; R Slamet Santoso (Journal of Public Policy and Management Review, 2019)
This research aims to describe the evaluation of roadside parking retribution policy in Semarang. The discussion was conducted because this policy is judged very important in order to local governments were able to dig up the resources and potential of the area which is owned to fullfill the needs of financing Government regions themselves, as the embodiment of an autonomous right which had owned. Semarang has so much potential that can be maximized to donate Original Income area (PAD) of the roadside parking retribution sector. And that is interesting to researched is the result of the implementation of roadside parking retribution policy in Semarang that so far has still not succeeded in reaching the target revenue levy regions. This research uses the qualitative method with type a descriptive research. The research site is in Semarang with the determination of the informant using the technique of purposive sampling. The data source in this research is the source of primary data and secondary data obtained from data collection techniques in the form of in-depth interviews and documents reviewing. The results obtained indicate that the roadside parking retribution as far is still seen as one of the Favorites of the original source of revenue (PAD) Area which certainly will be very loaded with conflict of interest from all parties is in it. It became one of the reasons why these policies greatly influence become so complicated and filled with a variety of issues in implementation. Similarly happened in the city of Semarang. Semarang City Government as State organizers so far assessed failed in implementing a policy of retribution on the edge of the street parking is generally the most noticeable, the issue can be seen is that the Government always fails Semarang meet the target achievement of roadside parking retribution. To achieve success, the city government officials through the Organization of Semarang is recommended to maximize its role in managing roadside parking, formulate the firmly and clearly policies, as well as maximizing the role of Academics in strategic studies with regard to policy of roadside parking retribution. In addition this course should also be the focus of the entire party is there, especially in this case is the community, to contribute to and build commitment in order to achieve the success of a policy of retribution on the curb parking in General the city of Semarang.